Can We Use Functional Genetics to Predict the Fate of Nitrogen in Estuaries? - Raes, Eric J.; Karsh, Kristen; Kessler, Adam J.; Cook, Perran L. M.; Holmes, Bronwyn H.; van de Kamp, Jodie; Bodrossy, Levente; Bissett, Andrew (Frontiers in Microbiology, 2020)
Increasing nitrogen (N) loads present a threat to estuaries, which are among the most heavily populated and perturbed parts of the world. N removal is largely mediated by the sediment microbial process of denitrification, in direct competition to dissimilatory nitrate reduction to ammonium (DNRA), which recycles nitrate to ammonium. Molecular indicators for N pathways are increasingly measured and analysed, but how robust and universal are they to quantify estuarine ‘health’ and capacity to process nutrient pollution? We analysed the diversity and community composition of sediment bacteria in 11 temperate estuaries covering 4 types of land use in Australia, and analysed how this might be used to constrain N removal. Our data suggest that sediment microbiomes play a central role in controlling the magnitude of the individual N removal rates in the 11 estuaries, however inclusion of relative gene abundance of 16S, nirS, and nrfA did not improve physicochemical measurement-based regression models to predict rates of denitrification and DNRA. Co-occurrence network analyses of the functional nirS denitrifying gene showed a greater modularity and a lower number of hubs in pristine sites compared to urban estuaries, suggesting a higher degree of niche partitioning in pristine estuaries. The distinctive differences between the urban and pristine network structures suggest that the nirS gene could be a likely gene candidate to understand the mechanisms by which these denitrifying communities form and respond to anthropogenic pressures.